CVIR Endovascular - Reekers, Jim
CVIR Endovascular is a multidisciplinary open access journal of the Cardiovascular and Interventional Radiological Society of Europe and the first open peer review journal in the field of endovascular interventions. The journal is intended for ALL specialists working in the field of endovascular treatment. CVIR Endovascular publishes manuscript in the area of venous and arterial interventions including vascular malformations, non-oncological embolization, peripheral vascular interventions, aortic interventions, emergency medicine and carotid interventions. CVIR Endovascular publishes a range of manuscript types including clinical investigations, systematic reviews, case reports, technical reports and video cases. The field of endovascular treatment is very dynamic and new ideas need rapid communication so that the latest information is available to treat our patients.  CVIR Endovascular also wants to stimulate scientific discussions and provides a podium to discuss your research work with your peers.